Student-led conferences : using portfolios to share learning with parents - Grant, Janet Millar (Ontario : Pembroke Publishers Ltd, 1995)
Shows teachers how to empower students to take responsibility for their own learning, evaluate their own work, and set their own goals. Offers advice on preparing students, responding to questions from parents, organizing a parent orientation night, developing portfolios, and following up.
Faculty
Keywords: Parent-teacher conferences; Teacher-student relationship